The Relationship between Drinking Water Sources and Nutritional Status of Elementary School Children on the Martapura Riverbank - Khatimah, Husnul; Mutttaqien, Fauzan; Fakhrurrazy, Fakhrurrazy; Arganita, Fidya Rahmadhany; Maulana, Irfan; Yuliana, Ida (Berkala Kedokteran, 2025)
Environment cleanliness has an indirect impact on nutritional status, particularly in the growth and development stages of children. In this study, school-age children living along the Martapura River's banks were asked to assess their nutritional health and the relationship between their drinking water sources. Study methodology employing a cross-sectional study design and analytical observational techniques. Research participants comprised 53 primary school students in grade 4 from SDN Keliling Benteng Ulu 2, SDN Keliling Benteng Tengah, and SDN Sungai Rangas Hambuku. Groups A (Martapura River water source group) and B (non-river water source group) comprised the seven groups of subjects: group 1 (very poor nutrition); group 2 (undernutrition); group 3 (normal nutrition); group 4 (obesity). Based on the data, it was discovered that 37 individuals (69.8%) had very poor nutritional status, and 39 individuals (73%), had the most commonly used gallons. The nutritional quality of primary school-aged children living along the Martapura Riverbanks did not significantly correlate with the sources of their drinking water, as indicated by the Fisher Exact test results, which revealed p = 0.146 (p > 0.05).